High-temperature-resistant titanium alloy powder material for additive manufacturing and preparation method of high-temperature-resistant titanium alloy powder material
By mixing and smelting various components under an inert atmosphere, a stable α-phase structure is formed, and the content of the β-phase is optimized through solid solution aging treatment, the problem of insufficient performance of existing titanium alloys at high strength and high temperatures is solved, high spherical shape, good fluidity and narrow particle size distribution are achieved, and the plasticity-strength matching and high temperature strength of the material are improved.
Patent Information
- Application Number
- CN202510220470.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing titanium alloy grades suitable for additive manufacturing are insufficient in the face of high strength and high temperature demands, which limits the development of titanium alloys in high-end applications.
Using a preparation method for high-temperature resistant titanium alloy powder material for additive manufacturing, a stable alpha phase structure is formed by mixing and melting various components in an inert atmosphere, including Al, Sn, Zr, Mo, Si, Nb, Ta, V, Cr, W, C, Fe, Ni, O, etc., and the content of the beta phase is optimized by solid solution aging treatment.
It realizes the high spherical shape, good fluidity and narrow particle size distribution of titanium alloys, improves the plastic-strength matching and high temperature strength of the material, enhances the mechanical properties and corrosion resistance of the parts, and meets more complex and rigorous application needs.
Smart Images

Figure CN119685654A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal powders, and more specifically, to a high-temperature resistant titanium alloy powder material for additive manufacturing and a preparation method thereof. Background Art
[0002] Additive manufacturing technology, also known as 3D printing technology, uses computer modeling software to design product models, and then builds solid parts by stacking materials layer by layer. This technology not only greatly broadens the freedom of design, but also significantly improves manufacturing efficiency and precision. Among them, selective laser melting (SLM) is a type of metal additive manufacturing technology, and with its unique technical advantages, it has shown great potential in the field of metal parts manufacturing.
[0003] SLM technology uses high-energy laser beams to precisely control the melting and solidification of metal powders layer by layer, achieving metallurgical bonding, thereby being able to directly manufacture complex structural metal parts with high dimensional accuracy and good surface quality. This technology not only breaks through the limitations of traditional manufacturing methods in terms of shape complexity, material utilization, and processing costs, but also has won a lot of attention and recognition for its high efficiency and environmental protection. It has currently shown great potential in many fields such as aerospace, medical, and automotive.
[0004] As a high-performance material, titanium alloy plays an irreplaceable role in aerospace, shipbuilding, medical implants and other fields due to its excellent strength-to-weight ratio, excellent corrosion resistance and high-temperature performance. However, the current titanium alloy grades suitable for additive manufacturing are relatively limited, which to some extent restricts the development of titanium alloy in high-end application fields.
[0005] Although titanium alloy grades such as TC4 and TA15 have excellent performance, their performance is often difficult to meet the requirements of higher strength, higher temperature or specific functions. Therefore, the development of new titanium alloy grades suitable for additive manufacturing has become an important research direction in the current field of materials science.
[0006] The patent application document with publication number CN107470610A discloses a titanium alloy powder material for 3D printing, which is composed of the following raw materials in parts by weight: 150-180 parts of titanium powder, 10-20 parts of cobalt powder, 6-12 parts of barium titanate, 5-10 parts of nano manganese dioxide, 3-8 parts of rosin, and 3-8 parts of palm wax.
[0007] The tensile strength of the blanks printed by a 3D printer from the titanium alloy powder prepared in the patent application document is low. Summary of the invention
[0008] In order to solve the above technical problems, the present application provides a high temperature resistant titanium alloy powder material for additive manufacturing and a preparation method thereof.
[0009] In the first aspect, the present application provides a method for preparing a high temperature resistant titanium alloy powder material for additive manufacturing, using the following technical solution: A method for preparing a high temperature resistant titanium alloy powder material for additive manufacturing comprises the following steps: S1: Raw material preparation: in terms of mass percentage, it includes the following components: Al: 4%~8%, Sn: 2%~5%, Zr: 0%~5%, Mo: 0.1%~1%, Si: 0.1%~1%, Nb: 0.1%~1%, Ta: 0.2%~1%, V: 0.01%~1%, Cr: 0.01%~1%, W: 0.2%~1%, C: 0.01%~0.1%, Fe: 0.01%~0.1%, Ni<0.1%, O<0.1%, and the rest is Ti, and the sum of the mass percentages of the above components is 100%; the Al is aluminum powder, and the aluminum powder is hydroxylated aluminum powder; Under an inert atmosphere, each component is mixed evenly according to the ratio, and then smelted and processed into a titanium alloy material; S2: Atomization powder making: In an inert atmosphere, the titanium alloy material is fed into the smelting chamber, and the smelting power is adjusted until the titanium alloy material forms a stable and continuous liquid flow, and an inert gas is used as an atomization medium for atomization powder making to obtain a prefabricated powder; S3: Screening: Under an inert atmosphere, the prefabricated powder is sent to a grading device for grading to obtain a high-temperature resistant titanium alloy powder material for additive manufacturing.
[0010] Preferably, in step S2, the smelting chamber and the atomizing chamber are evacuated and inert gas is introduced, the titanium alloy material is fed into the smelting chamber, and its rotation speed is controlled to be 8-10r / min; the smelting power is adjusted to 40-45kW, and when the titanium alloy material starts to drip, the smelting power is adjusted to 50-55kW until the titanium alloy material forms a stable and continuous liquid flow, and an inert gas is used as the atomizing medium for atomization and powdering, and the atomization pressure is controlled at 4.0-5.0MPa to obtain prefabricated powder.
[0011] Preferably, the flow rate of the atomizing medium is 1 to 3 times the speed of sound, and the speed of sound is 340 m / s.
[0012] Preferably, the heating temperature of the smelting chamber is 1600-1700°C.
[0013] Preferably, in step S2, before the titanium alloy material is fed into the smelting chamber, the smelting chamber is replaced with an inert gas for 2 to 3 times.
[0014] Preferably, in step S1, under an inert atmosphere, the components are uniformly mixed according to the ratio, and then smelted and processed into a titanium alloy bar with a diameter of 60-70 mm, a cone at one end and a thread at the other end.
[0015] Preferably, in step S2, when the smelting chamber and the atomizing chamber are evacuated, the vacuum degree is 10 -4 ~10 -6 Pa.
[0016] Preferably, in step S1, the raw material preparation further comprises, by mass percentage, 0.1% to 0.8% of a nucleating agent, wherein the nucleating agent is any one of zirconium diboride, titanium diboride and titanium carbide.
[0017] The beneficial effects of the present application are that by adding relatively more hydroxylated aluminum powder, Sn and other elements, and relatively small amounts of iron and carbon elements are compounded with nucleating agents, the alloy can form a large number of stable and fine α-phase structures in the subsequent processing process. These α-phase structures can maintain high strength in high temperature environments and effectively resist high-temperature deformation and damage. And compounding a small amount of Mo, Nb, Ta, V, Cr, W and other elements, these elements not only improve the strength of titanium alloys through the combined effects of solid solution strengthening and dispersion strengthening, but also effectively control the proportion of β-phase in the alloy. Through solid solution aging treatment, the content of β-phase is optimized to a reasonable range, which indirectly promotes the strengthening and regular distribution of α-phase. Hydroxylated aluminum powder and Sn stable α-phase structure provide a good toughness foundation for the alloy. At the same time, the addition of Zr element can refine the grain structure of the alloy, and further improve the toughness of the alloy through grain boundary strengthening. When the alloy is impacted by external force, the fine grains and stable α-phase structure can effectively prevent the expansion of cracks, thereby improving the fracture toughness of the alloy. The addition of a small amount of Si and C helps to form silicides and carbides. These compounds are dispersed in the matrix in the form of fine particles. They not only serve as the core of heterogeneous nucleation and optimize the nucleation position of the α phase, but also may further improve the strength and hardness of the alloy through dispersion strengthening.
[0018] Mixing the components under an inert atmosphere can effectively prevent the active elements in the raw materials from coming into contact with these impurity gases in the air, avoiding the formation of harmful inclusions or compounds during the raw material preparation stage, thereby ensuring the purity of the raw materials and laying the foundation for the subsequent preparation of high-quality high-temperature resistant titanium alloy powder materials.
[0019] Before the titanium alloy material is fed into the melting chamber, the melting chamber is replaced with an inert gas, which can effectively isolate harmful gases such as oxygen, thereby ensuring the chemical composition and original properties of the titanium alloy material, and ensuring the purity of the subsequent liquid flow and the obtained prefabricated powder. After the titanium alloy material forms a stable liquid flow, melting and atomizing at the same time can ensure that the composition of the titanium alloy powder is more uniform. The stable liquid flow is atomized under continuous supply, which can make the atomization process more stable, which helps to control the particle size, particle size distribution and sphericity of the powder, and in the subsequent additive manufacturing process, it can make the performance of the molded sample more uniform and stable.
[0020] Preferably, the preparation method of the aluminum hydroxylate powder is: evacuating the reaction chamber of the chemical vapor deposition equipment to a vacuum degree of 10 -4 ~10 -5 Pa, and introduce inert gas, then place aluminum powder in a reaction chamber of a chemical vapor deposition device, adjust the temperature of the reaction chamber to 400-500°C, introduce trimethylaluminum and water vapor at a flow ratio of 1:3-5, the reaction time is 2.5-4.5h, and cool and dry under an inert atmosphere to obtain hydroxylated aluminum powder, wherein the mass ratio of the aluminum powder, trimethylaluminum and water vapor is 100:6-10:1-3.
[0021] Beneficial effects: First, through chemical vapor deposition, under precisely controlled reaction conditions, the surface of aluminum powder can be relatively uniformly hydroxylated. When it is subsequently mixed with other materials (such as titanium powder, etc.) for the preparation of titanium alloy materials, uniform hydroxyls can provide consistent reaction active sites. In the preparation process such as smelting, atoms of different materials can diffuse and fuse with each other better with the help of these active sites, thereby forming a uniform and stable interface bond. This good interface bonding is like building a solid "bridge" inside the alloy, which enhances the connection strength between materials and avoids problems such as crack initiation and component segregation that may occur due to poor interface bonding, laying the foundation for subsequent titanium alloy materials to have excellent performance. Secondly, when the titanium alloy material is subsequently melted and atomized, in the molten state, the hydroxylated aluminum powder has an interaction between its surface hydroxyls and the surrounding alloy components. This interaction makes the surface energy distribution of the entire alloy melt more uniform, avoiding the situation where the local surface tension difference is too large. It is like putting a "uniformly stressed coat" on the alloy droplets. This uniform surface tension can cause the droplets to form particles that are closer to spherical. Powder materials with high sphericity have better fluidity during the 3D printing process and can be spread more evenly on the printing platform or the printed layer, thereby improving printing accuracy and quality.
[0022] Preferably, the Sn is tin powder, and the tin powder is modified tin powder. The preparation method of the modified tin powder is: evacuating the reaction chamber of the chemical vapor deposition equipment to a vacuum degree of 10-4 ~10 -5 Pa, and pass inert gas, then place tin powder in a reaction chamber of a chemical vapor deposition device, adjust the temperature of the reaction chamber to 400-500°C, pass trimethylaluminum and water vapor at a flow ratio of 1:3-5, the reaction time is 2-4 hours, and under an inert atmosphere, cool and dry to obtain modified tin powder, wherein the mass ratio of the tin powder, trimethylaluminum and water vapor is 100:2-4:1-3.
[0023] Beneficial effects: First, the hydroxylation of the surface of the modified tin powder and the presence of aluminum compounds can prevent oxygen from further contacting the tin atoms inside the tin powder, thereby effectively slowing down the oxidation rate of the tin powder. Secondly, in the subsequent process, the introduction of aluminum elements can form intermetallic compounds or strengthening phases between tin powder and elements such as titanium. The presence of these phases can effectively hinder dislocation movement, thereby enhancing the tensile strength of titanium alloys. At the same time, the distribution of compounds formed by aluminum elements and other elements at the grain boundaries can improve the bonding state of the grain boundaries, reduce stress concentration, and further enhance toughness, making the titanium alloy less likely to break when impacted.
[0024] Preferably, C is graphite powder, and the graphite powder is modified graphite powder. The preparation method of the modified graphite powder comprises the following steps: adding a hydrogen peroxide aqueous solution with a mass fraction of 30% to 50% and a pH of 3 to 4 to a reactor containing graphite powder, heating to 40 to 60° C., reacting for 1.5 to 2.5 hours, cooling, solid-liquid separation, washing, and drying to obtain modified graphite powder.
[0025] Preferably, the mass ratio of the graphite powder to the hydrogen peroxide solution is 1:10-20.
[0026] Beneficial effects: When the modified graphite powder is used to press titanium alloy materials, it can not only disperse better in the titanium alloy raw materials, but also form stronger chemical bonds or physical adsorption with other titanium alloy raw material particles, thereby enhancing the interface bonding force. In the subsequent process, it helps to transfer stress more effectively between the titanium alloy matrix and the graphite powder, so that the parts can withstand greater external forces without breaking, thereby improving the tensile strength and elongation.
[0027] At the same time, the modified graphite powder can also form a more refined microstructure in the titanium alloy matrix, play a role in heterogeneous nucleation, and promote the refinement of titanium alloy grains. The refined grain structure can improve the strength and toughness of the electrode and reduce brittleness. This is because the smaller grain size can increase the grain boundary area and hinder dislocation movement, thereby improving the strength and toughness of the material.
[0028] Preferably, step S1 also includes pre-treating the prepared titanium alloy material, and the pre-treatment includes the following steps: immersing the titanium alloy material in acetone under an inert atmosphere for 10 to 30 minutes, washing, and then immersing it in a sodium hydroxide solution with a mass fraction of 3% to 6% for 10 to 30 minutes, washing, and drying to obtain a pre-treated titanium alloy material.
[0029] Preferably, in step S3, the prefabricated powder is sent to a classification device for classification under an inert atmosphere, and then heated at 400-600°C and a vacuum degree of 10 -4 ~10 -5 Pa, vacuum degassing was carried out for 2 to 4 hours to obtain high temperature resistant titanium alloy powder material for additive manufacturing.
[0030] In a second aspect, the present application also provides a high temperature resistant titanium alloy powder material for additive manufacturing prepared by the above preparation method.
[0031] In summary, this application has the following beneficial effects: 1. The high-temperature resistant titanium alloy powder material for additive manufacturing prepared in this application exhibits better plasticity-strength matching and high-temperature strength, providing a new and effective way to strengthen and toughen titanium alloys.
[0032] 2. This application introduces titanium alloy materials prepared by hydroxylated aluminum powder through chemical vapor deposition. From the titanium alloy material stage to the powder material stage and then to the finished parts after 3D printing, each link has shown obvious advantages. In terms of the performance of titanium alloy powder materials, high sphericity, good fluidity and narrow particle size distribution are achieved; in the 3D printing process, key links such as powder laying and interlayer bonding are improved, and ultimately the printed parts have higher precision, better quality, and better mechanical properties and corrosion resistance. This all-round performance improvement makes it more competitive than traditional titanium alloy materials in many high-end manufacturing fields, and can meet more complex and demanding application requirements.
[0033] 3. The present application removes the impurity sources that may generate gas on the surface of the titanium alloy material by combining organic cleaning and alkaline cleaning, and vacuum degasses the screened pellets to ensure that the gas can be fully discharged from the pellets, thereby significantly reducing the oxygen content of the high-temperature resistant titanium alloy powder material for additive manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a metallographic image of sample 1 made of high temperature resistant titanium alloy powder material for additive manufacturing in Example 1 of the present application before solution treatment and aging; Figure 2 This is an electron microscope image of sample 1 made of high temperature resistant titanium alloy powder material for additive manufacturing in Example 1 of the present application before solution aging; Figure 3 This is an electron microscope image of sample 1 made of high temperature resistant titanium alloy powder material for additive manufacturing in Example 1 of the present application after solution treatment and aging; Figure 4 This is a metallographic image of a sample 12 made of high temperature resistant titanium alloy powder material for additive manufacturing before solid solution aging in Example 1 of the present application; Figure 5 This is an electron microscope image of the sample 12 made of high temperature resistant titanium alloy powder material for additive manufacturing in Example 1 of the present application before solution aging; Figure 6 This is an electron microscope image of the sample 12 made of high-temperature resistant titanium alloy powder material for additive manufacturing in Example 1 of the present application after solution treatment and aging. DETAILED DESCRIPTION
[0035] The present application is further described in detail below in conjunction with embodiments and preparation examples.
[0036] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0037] Silicon powder, with a purity of 99.9%, spherical shape, and a particle size distribution of 5-6 μm, was purchased from Hebei Teng Bimetallic Materials Co., Ltd.
[0038] Among them, the length of the titanium alloy bar is not higher than 900mm.
[0039] Test standards and instruments: Sphericity: The examples and comparative examples were tested according to GB / T16418-2008; Oxygen content: The examples and comparative examples were tested according to GB / T14265-93; Tensile strength: The embodiments and comparative examples were tested according to GB / T7314-2017; Yield strength: The embodiments and comparative examples were tested according to GB / T1591-2018; Elongation: The examples and comparative examples were tested according to GB / T-228.1-2010; Density: The embodiments and comparative examples were tested using a titanium alloy density tester AU-300S.
[0040] Preparation Example 1~3 Aluminum Hydroxide Powder Preparation Example 1 The reaction chamber of the chemical vapor deposition equipment was evacuated to a vacuum degree of 10 -4Pa, and introduce high-purity nitrogen, then evenly spread 1000g of aluminum powder on a material tray rotating at a low speed in the reaction chamber, the rotation speed is 10r / min, the temperature of the reaction chamber is adjusted to 400°C, trimethylaluminum and water vapor are introduced according to a flow ratio of 1:3, the flow rate of trimethylaluminum is 10sccm, the reaction time is 2.5h, and high-purity nitrogen is continued to be introduced to drop to room temperature, transferred to a vacuum drying oven, and dried at 110°C for 4h under a high-purity nitrogen atmosphere to obtain hydroxylated aluminum powder, wherein the mass ratio of the aluminum powder, trimethylaluminum and water vapor is 100:6:1.
[0041] Preparation Example 2 The reaction chamber of the chemical vapor deposition equipment was evacuated to a vacuum degree of 10 -4 Pa, and introduce high-purity nitrogen, then evenly spread 1000g of aluminum powder on a material tray rotating at a low speed in the reaction chamber, the rotation speed is 10r / min, the temperature of the reaction chamber is adjusted to 500°C, trimethylaluminum and water vapor are introduced according to a flow ratio of 1:5, the flow rate of trimethylaluminum is 12sccm, the reaction time is 4.5h, and high-purity nitrogen is continued to be introduced to drop to room temperature, transferred to a vacuum drying oven, and dried at 110°C for 6h under a high-purity nitrogen atmosphere to obtain hydroxylated aluminum powder, and the mass ratio of the aluminum powder, trimethylaluminum and water vapor is 100:10:3.
[0042] Preparation Example 3 The reaction chamber of the chemical vapor deposition equipment was evacuated to a vacuum degree of 10 -5 Pa, and introduce high-purity nitrogen, then evenly spread 1000g of aluminum powder on a material tray rotating at a low speed in the reaction chamber, the rotation speed is 10r / min, the temperature of the reaction chamber is adjusted to 450°C, trimethylaluminum and water vapor are introduced according to a flow ratio of 1:4, the flow rate of trimethylaluminum is 12sccm, the reaction time is 4h, and high-purity nitrogen is continued to be introduced to drop to room temperature, transferred to a vacuum drying oven, and dried at 110°C for 5h under a high-purity nitrogen atmosphere to obtain hydroxylated aluminum powder, and the mass ratio of the aluminum powder, trimethylaluminum and water vapor is 100:8:2.
[0043] Preparation Examples 4~6 Modified Tin Powder Preparation Example 4 The reaction chamber of the chemical vapor deposition equipment was evacuated to a vacuum degree of 10 -4 Pa, and introduce high-purity nitrogen, then evenly spread 500g of tin powder on a material tray rotating at a low speed in the reaction chamber, the rotation speed is 10r / min, the temperature of the reaction chamber is adjusted to 400°C, trimethylaluminum and water vapor are introduced according to a flow ratio of 1:3, the flow rate of trimethylaluminum is 10sccm, the reaction time is 2h, and high-purity nitrogen is continued to be introduced to drop to room temperature, transferred to a vacuum drying oven, and dried at 110°C for 3h under a high-purity nitrogen atmosphere to obtain modified tin powder, wherein the mass ratio of the tin powder, trimethylaluminum and water vapor is 100:2:1.
[0044] Preparation Example 5 The reaction chamber of the chemical vapor deposition equipment was evacuated to a vacuum degree of 10 -4 Pa, and introduce high-purity nitrogen, then evenly spread 500g of tin powder on a material tray rotating at a low speed in the reaction chamber, the rotation speed is 10r / min, the temperature of the reaction chamber is adjusted to 500°C, trimethylaluminum and water vapor are introduced according to a flow ratio of 1:5, the flow rate of trimethylaluminum is 12sccm, the reaction time is 5h, and high-purity nitrogen is continued to be introduced to drop to room temperature, transferred to a vacuum drying oven, and dried at 110°C for 5h under a high-purity nitrogen atmosphere to obtain modified tin powder, wherein the mass ratio of the tin powder, trimethylaluminum and water vapor is 100:4:3.
[0045] Preparation Example 6 The reaction chamber of the chemical vapor deposition equipment was evacuated to a vacuum degree of 10 -5 Pa, and introduce high-purity nitrogen, then evenly spread 500g of tin powder on a material tray rotating at a low speed in the reaction chamber, the rotation speed is 10r / min, the temperature of the reaction chamber is adjusted to 450°C, trimethylaluminum and water vapor are introduced according to a flow ratio of 1:4, the flow rate of trimethylaluminum is 12sccm, the reaction time is 3h, and high-purity nitrogen is continued to be introduced to drop to room temperature, transferred to a vacuum drying oven, and dried at 110°C for 4h under a high-purity nitrogen atmosphere to obtain modified tin powder, wherein the mass ratio of the tin powder, trimethylaluminum and water vapor is 100:3:2.
[0046] Preparation Examples 7~9 Modified Graphite Powder Preparation Example 7 Prepare a 30% mass fraction hydrogen peroxide aqueous solution, then use 8% mass fraction dilute nitric acid to adjust the pH to 3, then slowly add it dropwise into a reactor containing 10g of graphite powder, and continue to add and stir at 200r / min to mix evenly, heat to 40°C, stir and react for 2.5h, cool to room temperature, wash with pure water to neutral, then transfer to a vacuum drying oven, and dry at 80°C for 12h in a high-purity nitrogen atmosphere to obtain modified graphite powder.
[0047] The mass ratio of the graphite powder to the hydrogen peroxide solution is 1:20.
[0048] The graphite powder was dried at 80° C. for 4 h in a high-purity nitrogen atmosphere before use, and then ground and passed through a 200-mesh sieve.
[0049] Preparation Example 8 Prepare a 50% by mass aqueous solution of hydrogen peroxide, then use 8% by mass dilute nitric acid to adjust the pH to 4, then slowly add it dropwise to a reactor containing 10 g of graphite powder, and continue to add and stir at 200 r / min to mix evenly, heat to 60°C, stir to react for 1.5 hours, cool to room temperature, wash with pure water to neutral, then transfer to a vacuum drying oven, and dry at 80°C for 12 hours under a high-purity nitrogen atmosphere to obtain modified graphite powder.
[0050] The mass ratio of the graphite powder to the hydrogen peroxide solution is 1:10.
[0051] The graphite powder was dried at 80° C. for 4 h in a high-purity nitrogen atmosphere before use, and then ground and passed through a 200-mesh sieve.
[0052] Preparation Example 9 A 40% by mass aqueous solution of hydrogen peroxide was prepared, and then the pH value was adjusted to 3.5 with 8% by mass dilute nitric acid, and then slowly added dropwise to a reactor containing 10 g of graphite powder, and continued to add dropwise and stirred at 200 r / min to mix evenly, the temperature was raised to 50°C, stirred for reaction for 2.5 hours, cooled to room temperature, washed with pure water until neutral, and then transferred to a vacuum drying oven, and dried at 80°C for 12 hours in a high-purity nitrogen atmosphere to obtain modified graphite powder.
[0053] The mass ratio of the graphite powder to the hydrogen peroxide solution is 1:15.
[0054] The graphite powder was dried at 80° C. for 4 h in a high-purity nitrogen atmosphere before use, and then ground and passed through a 200-mesh sieve.
[0055] Preparation Example 10 Pretreatment of Silicon Powder Place the silicon powder evenly on the tray of the vacuum drying oven, close the door of the vacuum drying oven, start the vacuum pump, evacuate the drying oven to a vacuum state with a vacuum degree of 60Pa, introduce high-purity nitrogen at 3L / min for 10min, repeat the vacuuming and introduction of high-purity nitrogen 3 times to replace the atmosphere in the vacuum drying oven with high-purity nitrogen, then heat to 200°C at 2°C / min, maintain for 4h in a high-purity nitrogen atmosphere, stop heating, cool to 50°C, introduce high-purity nitrogen into the vacuum drying oven, and cool to room temperature to obtain pretreated silicon powder.
[0056] Example 1 This embodiment provides a method for preparing a high temperature resistant titanium alloy powder material for additive manufacturing, comprising the following steps: S1: Raw materials preparation: aluminum powder 550g, tin powder 330g, zirconium powder 245g, molybdenum powder 33g, silicon powder 30g, niobium powder 27g, tantalum powder 54g, vanadium powder 10g, chromium powder 10g, tungsten powder 50g, graphite powder 1.8g, iron powder 3.3g, nickel powder 2g, zirconium diboride 30g, titanium powder 8624g; In a high-purity argon atmosphere, the above powders were accurately weighed and mixed and ground for 5 hours according to the component ratio, stirred and mixed evenly, vacuum dried at 150°C for 4 hours, and then transferred to a mold, hot-pressed into a rod with a diameter of 70 mm at 300 MPa and 450°C, and further processed into a shape with a cone head at one end, a cone angle of 70°, and a threaded shape at the other end to obtain a titanium alloy rod; S2: Melting and atomization: The melting chamber and atomization chamber are evacuated to a vacuum degree of 10 -4 Pa, and introduce high-purity argon gas to keep the internal pressure slightly higher than atmospheric pressure (1.02~1.05 times atmospheric pressure), send the conical tip of the titanium alloy bar into the melting chamber, control its rotation speed to 8r / min, turn on the medium frequency power operation button, adjust the melting power to about 40kW, when the bar melts to drip, slowly increase the melting power to 50kW, the titanium alloy bar forms a stable and continuous liquid flow, click the down button, adjust the feeding speed to 35mm / min, where the temperature of the melting chamber is about 1600℃; Then, the silo air supply valve and air supply hand valve are opened, the atomization high-pressure stop valve and the atomization high-pressure air hand valve are opened, the pressure is opened to about 4.0~4.2Mpa, the induced draft fan is turned on, the smelting chamber pressure is adjusted to 35Kpa, the atomization chamber pressure is adjusted to 0Kpa, the atomization pressure is adjusted to 4.5Mpa, and high-purity argon gas is introduced at a flow rate of 680m / s, so that the formed metal droplets are quickly cooled and collected in the cooling device to obtain prefabricated powder; S3: Classification: Under argon atmosphere, ensure that the induced draft fan operates in a balanced and stable state, turn on the primary and secondary classifying wheels, with the primary classifying wheel at 25 Hz / rev and the secondary classifying wheel at 20 Hz / rev, and send the prefabricated powder into the classifying equipment for particle size classification to obtain pellets with a particle size distribution of 15-53 μm, which are high-temperature resistant titanium alloy powder materials for additive manufacturing, and are prepared for filling in plastic bottles.
[0057] The particle size distribution of the raw materials is 1~100μm; the aluminum powder is hydroxylated aluminum powder, which comes from Preparation Example 1; the silicon powder is pretreated silicon powder, which comes from Preparation Example 10.
[0058] The yield of high temperature resistant titanium alloy powder material for additive manufacturing is 40.0%, the sphericity is 97.0%, and the oxygen content is 980ppm.
[0059] Example 2 The difference between this embodiment and embodiment 1 is that: S1: Raw materials preparation: aluminum powder 700g, tin powder 330g, zirconium powder 245g, molybdenum powder 33g, silicon powder 30g, niobium powder 27g, tantalum powder 54g, vanadium powder 10g, chromium powder 10g, tungsten powder 50g, graphite powder 1.8g, iron powder 3.3g, nickel powder 2g, zirconium diboride 30g, titanium powder 8474g; The aluminum powder is hydroxylated aluminum powder, which comes from Preparation Example 2.
[0060] The rest is the same as in Example 1.
[0061] The yield of high temperature resistant titanium alloy powder material for additive manufacturing is 36.0%, the sphericity is 98.2%, and the oxygen content is 968ppm.
[0062] Example 3 The difference between this embodiment and embodiment 2 is that: S1: Raw materials preparation: aluminum powder 400g, tin powder 200g, zirconium powder 500g, molybdenum powder 10g, silicon powder 10g, niobium powder 10g, tantalum powder 20g, vanadium powder 1g, chromium powder 1g, tungsten powder 20g, graphite powder 5g, iron powder 1g, nickel powder 5g, zirconium diboride 80g, titanium powder 8737g; In a high-purity argon atmosphere, the above powders were accurately weighed and mixed and ground for 5 hours according to the component ratio, stirred and mixed evenly, vacuum dried at 150°C for 4 hours, and then transferred to a mold, hot-pressed into a rod with a diameter of 60 mm at 350 MPa and 500°C, and further processed into a shape with a cone head at one end, a cone angle of 70°, and a threaded shape at the other end to obtain a titanium alloy rod; S2: Melting and atomization: The melting chamber and atomization chamber are evacuated to a vacuum degree of 10 -6 Pa, and introduce high-purity argon gas to keep the internal pressure slightly higher than atmospheric pressure (1.02~1.05 times atmospheric pressure), send the conical tip of the titanium alloy bar into the melting chamber, control its rotation speed to 10r / min, turn on the medium frequency power operation button, adjust the melting power to about 45kW, when the bar melts to drip, slowly increase the melting power to 55kW, the titanium alloy bar forms a stable and continuous liquid flow, click the down button, adjust the feeding speed to 35mm / min, where the temperature of the melting chamber is about 1700℃; Then, the silo air supply valve and air supply hand valve are opened, the atomization high-pressure stop valve and the atomization high-pressure air hand valve are opened, the pressure is opened to about 4.0~4.2Mpa, the induced draft fan is turned on, the smelting chamber pressure is adjusted to 45Kpa, the atomization chamber pressure is adjusted to 5Kpa, the atomization pressure is adjusted to 4.0Mpa, and high-purity argon gas is introduced at a flow rate of 340m / s, so that the formed metal droplets are quickly cooled and collected in the cooling device to obtain prefabricated powder; The aluminum powder is hydroxylated aluminum powder, which comes from Preparation Example 3.
[0063] The rest is the same as in Example 2.
[0064] The yield of high-temperature resistant titanium alloy powder material for additive manufacturing is 44.1%, the sphericity is 98.5%, and the oxygen content is 951ppm.
[0065] Example 4 The difference between this embodiment and embodiment 3 is that: S1: Raw materials preparation: aluminum powder 800g, tin powder 500g, molybdenum powder 100g, silicon powder 100g, niobium powder 100g, tantalum powder 100g, vanadium powder 100g, chromium powder 100g, tungsten powder 100g, graphite powder 10g, iron powder 10g, nickel powder 6g, zirconium diboride 10g, titanium powder 7964g; In a high-purity argon atmosphere, the above powders were accurately weighed and mixed and ground for 5 hours according to the component ratio, stirred and mixed evenly, vacuum dried at 150°C for 4 hours, and then transferred to a mold, hot-pressed into a rod with a diameter of 70 mm at 350 MPa and 500°C, and further processed into a shape with a cone head at one end, a cone angle of 70°, and a threaded shape at the other end to obtain a titanium alloy rod; S2: Melting and atomization: The melting chamber and atomization chamber are evacuated to a vacuum degree of 10 -5 Pa, and then slowly introduce high-purity argon gas to keep the internal pressure slightly higher than atmospheric pressure (1.02~1.05 times atmospheric pressure). After reaching the set pressure, stop ventilation and let the gas mix in a static closed state for 10 minutes, then open the exhaust valve to discharge part of the mixed gas, and repeat this cycle twice. Then send the conical tip of the titanium alloy bar into the melting chamber, control its rotation speed to 9r / min, turn on the medium frequency power supply operation button, adjust the melting power to about 45kW, and when the bar melts to drip, slowly increase the melting power to 50kW, the titanium alloy bar forms a stable and continuous liquid flow, click the down button, and adjust the feeding speed to 35mm / min. The temperature of the melting chamber is about 1650℃; Then, the silo air supply valve and air supply hand valve are opened, the atomization high-pressure stop valve and the atomization high-pressure air hand valve are opened, the pressure is opened to about 4.0~4.2Mpa, the induced draft fan is turned on, the smelting chamber pressure is adjusted to 40Kpa, the atomization chamber pressure is adjusted to 2Kpa, the atomization pressure is adjusted to 5.0Mpa, and high-purity argon gas is introduced at a flow rate of 1020m / s, so that the formed metal droplets are quickly cooled and collected in the cooling device to obtain prefabricated powder; The aluminum powder is hydroxylated aluminum powder, which comes from Preparation Example 3.
[0066] The rest is the same as in Example 3.
[0067] The yield of high-temperature resistant titanium alloy powder material for additive manufacturing is 53%, the sphericity is 96.3%, and the oxygen content is 933ppm.
[0068] Example 5 This embodiment provides a method for preparing a high temperature resistant titanium alloy powder material for additive manufacturing, comprising the following steps: S1: Raw materials preparation: aluminum powder 550g, tin powder 330g, zirconium powder 245g, molybdenum powder 33g, silicon powder 30g, niobium powder 27g, tantalum powder 54g, vanadium powder 10g, chromium powder 10g, tungsten powder 50g, graphite powder 1.8g, iron powder 3.3g, nickel powder 2g, titanium diboride 10g, titanium powder 8644g; In a high-purity argon atmosphere, the above powders are accurately weighed and mixed and ground for 5 hours according to the component ratio, stirred and mixed evenly, vacuum dried at 150°C for 4 hours, and then transferred to a mold, hot pressed into a rod with a diameter of 70 mm at 300Mpa and 450°C, and further processed into a shape with a cone head at one end, a cone angle of 70°, and a threaded shape at the other end, immersed in acetone for 10 minutes in a high-purity argon atmosphere, and gently brushed with a soft brush, and then immersed in a sodium hydroxide solution with a mass fraction of 6%. After 10 minutes, it is washed with pure water until neutral, transferred to a vacuum drying oven, and dried at 110°C for 12 hours in a high-purity nitrogen atmosphere, and cooled to room temperature to obtain a titanium alloy rod; S2: Melting and atomization: The melting chamber and atomization chamber are evacuated to a vacuum degree of 10 -5 Pa, and then slowly introduce high-purity argon gas to keep the internal pressure slightly higher than atmospheric pressure (1.02~1.05 times atmospheric pressure). After reaching the set pressure, stop ventilation and let the gas mix in a static closed state for 10 minutes, then open the exhaust valve to discharge part of the mixed gas, and repeat this cycle 3 times. Then send the conical tip of the titanium alloy bar into the melting chamber, control its rotation speed to 9r / min, turn on the medium frequency power supply operation button, adjust the melting power to about 45kW, and when the bar melts to dripping, slowly increase the melting power to 50kW, the titanium alloy bar forms a stable and continuous liquid flow, and adjust the feeding speed to 35mm / min. The temperature of the melting chamber is about 1650℃; Then, the silo air supply valve and air supply hand valve are opened, the atomization high-pressure stop valve and the atomization high-pressure air hand valve are opened, the pressure is opened to about 4.0~4.2Mpa, the induced draft fan is turned on, the smelting chamber pressure is adjusted to 35Kpa, the atomization chamber pressure is adjusted to 0Kpa, the atomization pressure is adjusted to 4.5Mpa, and high-purity argon gas is introduced at a flow rate of 680m / s, so that the formed metal droplets are quickly cooled and collected in the cooling device to obtain prefabricated powder; S3: Classification: Under argon atmosphere, ensure that the induced draft fan operates in a balanced and stable state, turn on the first and second classifying wheels, with the first classifying wheel at 25 Hz / rev and the second classifying wheel at 20 Hz / rev, send the prefabricated powder into the classification equipment for particle size classification, and screen out particles with a particle size distribution of 15~53μm, which are titanium alloy powder materials for additive manufacturing, and use plastic bottles for filling.
[0069] Among them, the particle size distribution of the raw materials is 1~100μm; the aluminum powder is hydroxylated aluminum powder, which comes from Preparation Example 3, the silicon powder is pretreated silicon powder, which comes from Preparation Example 10; the tin powder is modified tin powder, which comes from Preparation Example 4.
[0070] The yield of titanium alloy powder material for additive manufacturing is 42.3%, the sphericity is 97.4%, and the oxygen content is 941ppm.
[0071] Example 6 The difference between this embodiment and embodiment 5 is that: S1: Raw materials preparation: aluminum powder 550g, tin powder 330g, zirconium powder 245g, molybdenum powder 33g, silicon powder 30g, niobium powder 27g, tantalum powder 54g, vanadium powder 10g, chromium powder 10g, tungsten powder 50g, graphite powder 1.8g, iron powder 3.3g, nickel powder 2g, titanium carbide 10g, titanium powder 8644g; In a high-purity argon atmosphere, the above powders were accurately weighed and mixed and ground for 5 hours according to the component ratio, stirred and mixed evenly, vacuum dried at 150°C for 4 hours, and then transferred to a mold, hot pressed into a rod with a diameter of 70 mm at 300 MPa and 450°C, and further processed into a shape with a cone head at one end, a cone angle of 70°, and a threaded shape at the other end, immersed in acetone for 30 minutes in a high-purity argon atmosphere, and gently brushed with a soft brush, and then immersed in a sodium hydroxide solution with a mass fraction of 3%. After 30 minutes, it was washed with pure water until neutral, transferred to a vacuum drying oven, dried at 110°C for 12 hours in a high-purity nitrogen atmosphere, and cooled to room temperature to obtain a titanium alloy rod; S3: Classification: Under argon atmosphere, ensure that the induced draft fan operates in a balanced and stable state, turn on the first and second classifying wheels, the first classifying wheel 25Hz / rev, the second classifying wheel 20Hz / rev, send the prefabricated powder into the classification equipment for particle size classification, screen out particles with a particle size distribution of 15~53μm, and then heat at 400℃ and vacuum degree 10 -4 Pa, vacuum degassing was carried out for 2 h, and then the temperature was lowered to obtain titanium alloy powder material for additive manufacturing, which was then filled into plastic bottles for use.
[0072] The tin powder is modified tin powder, and the modified tin powder comes from Preparation Example 5; the graphite powder is modified graphite powder, and the modified graphite powder comes from Preparation Example 7.
[0073] The yield of titanium alloy powder material for additive manufacturing is 43.7%, the sphericity is 97.7%, and the oxygen content is 922ppm.
[0074] The rest is the same as Example 5.
[0075] Example 7 The difference between this embodiment and embodiment 6 is that: S3: Classification: Under argon atmosphere, ensure that the induced draft fan operates in a balanced and stable state, turn on the first and second classifying wheels, the first classifying wheel 25Hz / rev, the second classifying wheel 20Hz / rev, send the prefabricated powder into the classification equipment for particle size classification, screen out particles with a particle size distribution of 15~53μm, and then heat at 600℃ and vacuum degree 10 -5 Pa, vacuum degassing was carried out for 4 hours, and then the temperature was lowered to obtain titanium alloy powder material for additive manufacturing, which was then filled in plastic bottles for use.
[0076] The aluminum powder is hydroxylated aluminum powder, which is obtained from Preparation Example 3; the tin powder is modified tin powder, which is obtained from Preparation Example 6; and the graphite powder is modified graphite powder, which is obtained from Preparation Example 8.
[0077] The yield of titanium alloy powder material for additive manufacturing is 44.8%, the sphericity is 98.1%, and the oxygen content is 892ppm.
[0078] The rest is the same as Example 6.
[0079] Example 8 The difference between this embodiment and embodiment 7 is that: The aluminum powder is hydroxylated aluminum powder, which is obtained from Preparation Example 3; the tin powder is modified tin powder, which is obtained from Preparation Example 6; and the graphite powder is modified graphite powder, which is obtained from Preparation Example 9.
[0080] The yield of titanium alloy powder material for additive manufacturing is 45.2%, the sphericity is 98.2%, and the oxygen content is 886ppm.
[0081] The rest is the same as Example 7.
[0082] Comparative Example 1 The difference between this comparative example and Example 1 is: In step S1, the raw materials are prepared: 550g aluminum powder, 330g tin powder, 245g zirconium powder, 33g molybdenum powder, 30g silicon powder, 27g niobium powder, 54g tantalum powder, 10g vanadium powder, 10g chromium powder, 50g tungsten powder, 1.8g graphite powder, 3.3g iron powder, 2g nickel powder, and 8654g titanium powder; The rest is the same as in Example 1.
[0083] The yield of titanium alloy powder material for additive manufacturing is 37.6%, the sphericity is 94.8%, and the oxygen content is 1058ppm.
[0084] Comparative Example 2 The difference between this comparative example and Example 1 is: In step S1, the raw materials are prepared: 550g aluminum powder, 330g tin powder, 245g zirconium powder, 33g molybdenum powder, 30g silicon powder, 27g niobium powder, 54g tantalum powder, 10g vanadium powder, 10g chromium powder, 50g tungsten powder, 1.8g graphite powder, 3.3g iron powder, 2g nickel powder, 30g zirconium diboride, and 8624g titanium powder; Among them, the aluminum powder was not hydroxylated and the silicon powder was not pretreated.
[0085] The rest is the same as in Example 1.
[0086] The yield of titanium alloy powder material for additive manufacturing is 39.4%, the sphericity is 95.6%, and the oxygen content is 994ppm.
[0087] Performance Testing (1) Detection 1 S11: Build a 3D model using modeling software, set printing parameters and plan the printing path using slicing software; S12: The titanium alloy powder materials for additive manufacturing (hereinafter referred to as titanium alloy powder materials) prepared in Examples 1 to 8 and Comparative Examples 1 to 2 are respectively placed in an SLM printer, and the printing parameters are set as follows: laser power of 400 W, scanning speed of 1200 mm / s, scanning spacing of 0.1 mm, layer thickness of 0.03 mm, substrate preheating temperature of 100°C, adjacent layer rotation angle of 90°, and strip scanning strategy; then printing is started, and after printing is completed, it is separated from the substrate by wire cutting, and the residual powder is cleaned to obtain a printed part; S13: Under an argon atmosphere, each printed part is placed in a heating furnace, and the temperature is raised to 980°C at a rate of 5°C / min, and kept at this temperature for 2 hours. The furnace door is opened, and the parts are placed in the air to cool naturally, thereby obtaining pre-treated samples; S14: Under an argon atmosphere, each pretreated sample is transferred into an aging furnace, and the temperature is raised to 700°C at 3°C / min, kept at this temperature for 4 hours, and cooled with the furnace to obtain samples, which are marked as samples 1 to 10 in sequence.
[0088] Each sample was tested and the test results are shown in Table 1.
[0089] Table 1 Tensile performance test data of samples 1-10 made of titanium alloy powder materials in Examples 1-8 and Comparative Examples 1-2
[0090] (2) Test 2 S11: Build a 3D model using modeling software, set printing parameters and plan the printing path using slicing software; S12: The titanium alloy powder material prepared in Example 1 is placed in an SLM printer, and the printing parameters are set as follows: laser power of 400 W, scanning speed of 1200 mm / s, scanning spacing of 0.1 mm, layer thickness of 0.03 mm, substrate preheating temperature of 100°C, adjacent layer rotation angle of 90°, and strip scanning strategy; then printing is started, and after printing is completed, it is separated from the substrate by wire cutting, and the residual powder is cleaned to obtain a printout; S13: Under an argon atmosphere, each printed part is placed in a heating furnace, and the temperature is raised to 980°C at a rate of 5°C / min, and kept at this temperature for 3 hours. The furnace door is opened, and the parts are placed in the air for natural cooling to obtain pre-treated samples; S14: Under an argon atmosphere, each pretreated sample is transferred into an aging furnace, heated to 700°C at 3°C / min, kept at that temperature for 4 hours, and cooled with the furnace to obtain a sample, which is marked as sample 11.
[0091] The samples were tested and the test results are shown in Table 2.
[0092] Table 2 Tensile performance test data of sample 11 made of titanium alloy powder material in Example 1
[0093] (3) Test three S11: Build a 3D model using modeling software, set printing parameters and plan the printing path using slicing software; S12: The titanium alloy powder material prepared in Example 1 is placed in an SLM printer, and the printing parameters are set as follows: laser power of 430 W, scanning speed of 1200 mm / s, scanning spacing of 0.1 mm, layer thickness of 0.03 mm, substrate preheating temperature of 100° C., adjacent layer rotation angle of 67°, and strip scanning strategy; then printing is started, and after printing is completed, it is separated from the substrate by wire cutting, and the residual powder is cleaned to obtain a printed part; S13: Under an argon atmosphere, each printed part is placed in a heating furnace, and the temperature is raised to 980°C at a rate of 5°C / min, and kept at this temperature for 2 hours. The furnace door is opened, and the parts are placed in the air to cool naturally, thereby obtaining pre-treated samples; S14: Under an argon atmosphere, each pretreated sample is transferred into an aging furnace, heated to 700°C at 3°C / min, kept at this temperature for 4 hours, and cooled with the furnace to obtain a sample, which is marked as sample 12.
[0094] Among them, after solution aging treatment, there are no obvious defects on the surface of sample 12.
[0095] The samples were tested and the test results are shown in Table 3.
[0096] Table 3 Tensile performance test data of sample 12 made of titanium alloy powder material in Example 1
[0097] By comparing and analyzing Tables 1 to 3, under different test parameters, the tensile performance test data of Samples 1, 11 and 12 made of titanium alloy powder materials in Example 1 show that: Comparative analysis of sample 1 and sample 11 shows that: when the tensile properties are tested at 25°C, the tensile strength and yield strength of the prepared samples are reduced, and the elongation is increased. This is because: appropriately extending the holding time in step S13 will give the solute atoms more time to diffuse. Some solute atoms may precipitate at the grain boundaries to form second-phase particles. If the size of these second-phase particles is large or unevenly distributed, they will become a source of stress concentration and reduce the tensile strength of the sample. At the same time, the diffusion of solute atoms and the formation of second-phase particles will change the internal structure of the material, change the resistance to dislocation movement, promote dislocation movement to a certain extent, and lead to an increase in the elongation of the material.
[0098] Comparative analysis of sample 1 and sample 12 shows that the tensile strength, yield strength and elongation of the samples obtained by increasing the laser power of the SLM printer and reducing the rotation angle of adjacent layers are all reduced. This is because: at higher laser power, metal atoms have more time and energy to diffuse, and it is easy to form larger grains. On the one hand, coarse grains reduce the grain boundaries relatively. Although dislocations are easier to move, this movement lacks effective constraints. When subjected to force, the internal structure of the material cannot effectively coordinate deformation, resulting in a decrease in the overall resistance to deformation and a decrease in tensile strength. At the same time, it is difficult for the large grain structure to evenly disperse stress through the coordination of grain boundaries. The stress concentration phenomenon in local areas is aggravated, and the material undergoes local deformation and microcrack initiation prematurely, which limits the improvement of elongation and causes a decrease in elongation. On the other hand, excessive laser power may also cause some defects in the printing process, such as pores and cracks. These defects, as stress concentration points, greatly weaken the bearing capacity of the material, making the sample prone to local deformation and fracture under lower stress, seriously affecting the tensile strength and yield strength, and also hindering the uniform deformation of the material as a whole, resulting in a decrease in elongation.
[0099] When the rotation angle of adjacent layers is reduced, the texture in the printing direction will be more obvious, and the difference in the material's ability to resist tensile forces in different directions will increase. This anisotropy makes it easier for the material to break locally in the direction with weaker resistance to tensile forces during the stretching process, and the overall bearing capacity of the material cannot be fully utilized, which leads to a decrease in tensile strength and yield strength. In addition, due to the early occurrence of local fractures, the material cannot achieve sufficient overall plastic deformation, and the overall elongation decreases accordingly.
[0100] By comparing and analyzing the tensile performance test data of the samples made of titanium alloy powder materials in different embodiments and comparative examples in Table 1, it can be seen that: From the tensile performance test data of samples 1 to 4 made of titanium alloy powder materials in Examples 1 to 4 and the tensile performance test data of samples 9 to 10 made of titanium alloy powder materials in Comparative Examples 1 to 2, it can be seen that by properly adjusting the ratio of each component in the raw material, the tensile performance of the samples made of titanium alloy powder materials is maintained within a good range. This is because by changing the ratio of alloying elements, the distribution and amount of strengthening phases can be optimized, the formation of coarse grains can be reduced, and the material can be guaranteed to withstand external forces evenly during the stretching process, preventing local premature fracture, and maintaining the tensile performance at a good level.
[0101] After the nucleating agent is added, a large number of heterogeneous nucleation points are provided during melt atomization, which enables the alloy to form more fine and uniform grains during the solidification process. During the atomization process, the fine grains make the microstructure of the titanium alloy powder material more uniform, improving the tensile properties of subsequent samples. This is because fine grains are conducive to the diffusion and fusion of atoms, making the connection between layers stronger. When the sample is subjected to tensile force, it can better transfer the external force to the entire structure to avoid interlayer separation. In addition, the fine grains and uniform structure can effectively hinder the movement of dislocations during the stretching process, allowing the sample to withstand higher tensile forces and reduce excessive plastic deformation.
[0102] From the tensile properties test data of samples 4 to 8 made of titanium alloy powder materials in Examples 4 to 8, it can be seen that by modifying the tin powder and graphite powder, the tin powder modification enhances the interface bonding force, and the graphite powder modification improves the microstructure and lubrication properties, so that the subsequent samples can transfer stress more evenly during stretching, more effectively resist dislocation movement, and may have better stress relief capabilities, thereby improving both the tensile strength and elongation.
[0103] Combination Figures 1 to 6 It can be seen that from the metallographic images of samples 1 and 12 made of the titanium alloy powder material in Example 1 before solution aging treatment (i.e., prints), it can be seen that the metallographic image of sample 12 before solution aging treatment shows relatively more defects, such as pores. This may be due to the increase in laser power and the decrease in rotation angle, which on the one hand increases the molten pool temperature, increases the depth, changes the solidification rate, etc., which may lead to changes in gas generation and discharge, thereby increasing the probability of pore formation; on the other hand, the increase in laser power and the decrease in rotation angle will also affect the uniformity of the spreading and stacking of the titanium alloy powder material on the substrate, resulting in changes in the interaction between the laser beam and the titanium alloy powder material, which may lead to irregular shape of the molten pool and uneven temperature distribution, etc., which may affect the formation and distribution of pores, thereby reducing the mechanical properties of sample 12.
[0104] From the SEM images of the samples 1 and 12 made of the titanium alloy powder material in Example 1 before and after the solution aging treatment, it can be seen that the morphology is basically the same. After the solution aging treatment, both contain strip structures with a large aspect ratio. Due to their slender shape, they can hinder the movement of dislocations and increase the resistance to dislocation slip, thereby improving the strength of the material. Among them, there are also fine and dispersed needle structures distributed between the strip structures with a large aspect ratio. On the one hand, they can serve as obstacles to the movement of dislocations, increase the resistance to dislocation slip, and together with the strip structures with a large aspect ratio, they form a dense obstacle network, making it difficult for dislocations to move, thereby effectively improving the strength of the material. On the other hand, it can also prevent the expansion of cracks. The fine and dispersed needle structures can be nailed on the crack expansion path like nails, so that the crack needs to consume more energy during the propagation process. This energy consumption improves the overall toughness of the material, that is, the material can absorb more energy without breaking when subjected to force.
Claims
1. A method for preparing a high temperature resistant titanium alloy powder material for additive manufacturing, characterized in that: The steps include: S1: Raw material preparation: in terms of mass percentage, it includes the following components: Al: 4%~8%, Sn: 2%~5%, Zr: 0%~5%, Mo: 0.1%~1%, Si: 0.1%~1%, Nb: 0.1%~1%, Ta: 0.2%~1%, V: 0.01%~1%, Cr: 0.01%~1%, W: 0.2%~1%, C: 0.01%~0.1%, Fe: 0.01%~0.1%, Ni<0.1%, O<0.1%, nucleating agent: 0.1%~0.8%, and the rest is Ti, and the sum of the mass percentages of the above components is 100%; the Al is aluminum powder, and the aluminum powder is hydroxylated aluminum powder; the nucleating agent is any one of zirconium diboride, titanium diboride, and titanium carbide; Under an inert atmosphere, each component is mixed evenly according to the ratio, and then smelted and processed into a titanium alloy material; S2: Atomization powder making: In an inert atmosphere, the titanium alloy material is fed into the smelting chamber, and the smelting power is adjusted until the titanium alloy material forms a stable and continuous liquid flow, and an inert gas is used as an atomization medium for atomization powder making to obtain a prefabricated powder; S3: Screening: Under an inert atmosphere, the prefabricated powder is sent to a grading device for grading to obtain a high temperature resistant titanium alloy powder material for additive manufacturing; The preparation method of the aluminum hydroxylate powder is as follows: evacuating the reaction chamber of the chemical vapor deposition equipment to a vacuum degree of 10 -4 ~10 -5 Pa, and introduce inert gas, then place aluminum powder in a reaction chamber of a chemical vapor deposition device, adjust the temperature of the reaction chamber to 400-500°C, introduce trimethylaluminum and water vapor at a flow ratio of 1:3-5, the reaction time is 2.5-4.5h, and cool and dry under an inert atmosphere to obtain hydroxylated aluminum powder, wherein the mass ratio of the aluminum powder, trimethylaluminum and water vapor is 100:6-10:1-3.
2. The preparation method according to claim 1, characterized in that: In step S2, before the titanium alloy material is fed into the smelting chamber, the smelting chamber is replaced with an inert gas for 2 to 3 times.
3. The preparation method according to claim 2, characterized in that: The flow rate of the atomized medium is 1 to 3 times the speed of sound, and the speed of sound is 340 m / s.
4. The preparation method according to claim 1, characterized in that: The Sn is tin powder, and the tin powder is modified tin powder. The preparation method of the modified tin powder is: evacuating the reaction chamber of the chemical vapor deposition equipment to a vacuum degree of 10 -4 ~10 -5 Pa, and pass inert gas, then place tin powder in a reaction chamber of a chemical vapor deposition device, adjust the temperature of the reaction chamber to 400-500°C, pass trimethylaluminum and water vapor at a flow ratio of 1:3-5, the reaction time is 2-4 hours, and under an inert atmosphere, cool and dry to obtain modified tin powder, wherein the mass ratio of the tin powder, trimethylaluminum and water vapor is 100:2-4:1-3.
5. The preparation method according to claim 1, characterized in that: The C is graphite powder, and the graphite powder is modified graphite powder. The preparation method of the modified graphite powder comprises the following steps: adding a hydrogen peroxide aqueous solution with a mass fraction of 30% to 50% and a pH of 3 to 4 into a reactor containing graphite powder, heating to 40 to 60° C., reacting for 1.5 to 2.5 hours, cooling, solid-liquid separation, washing, and drying to obtain modified graphite powder.
6. The preparation method according to claim 1, characterized in that: Step S1 also includes pre-treating the prepared titanium alloy material, and the pre-treatment includes the following steps: immersing the titanium alloy material in acetone under an inert atmosphere for 10 to 30 minutes, washing, and then immersing it in a sodium hydroxide solution with a mass fraction of 3% to 6% for 10 to 30 minutes, washing, and drying to obtain a pre-treated titanium alloy material.
7. The preparation method according to claim 1, characterized in that: In step S3, the prefabricated powder is sent to a classification device for classification under an inert atmosphere, and then heated at 400-600°C and a vacuum degree of 10 -4 ~10 -5 Pa, vacuum degassing was carried out for 2 to 4 hours to obtain high temperature resistant titanium alloy powder material for additive manufacturing.
8. The preparation method according to claim 1, characterized in that: The Si is silicon powder, which undergoes the following pretreatment steps before use: Place the silicon powder evenly on the tray of the vacuum drying oven, close the door of the vacuum drying oven, start the vacuum pump, evacuate the drying oven to a vacuum state with a vacuum degree of 60Pa, introduce high-purity nitrogen at 3L / min for 10min, repeat the vacuuming and introduction of high-purity nitrogen 3 times to replace the atmosphere in the vacuum drying oven with high-purity nitrogen, then heat to 200°C at 2°C / min, maintain for 4h in a high-purity nitrogen atmosphere, stop heating, cool to 50°C, introduce high-purity nitrogen into the vacuum drying oven, and cool to room temperature to obtain pretreated silicon powder.
9. A high temperature resistant titanium alloy powder material for additive manufacturing obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Titanium alloy powder material used for 3D printing
CN107470610A
Gas atomization preparation method of fine spherical titanium or titanium alloy powder
CN103846447A
Manufacturing method of micro spherical titanium and titanium alloy powder
CN104475743A
Preparation method for titanium alloy powder for 3D printing
CN110684899A
Method for manufacturing aluminum from aluminum hydroxides containing silicic acid, titanic acid and iron
CN1158914A
Cited By
Preparation method of ultrahigh-strength plastic titanium alloy with yield strength larger than 1500 MPa
CN121178873A
Titanium alloy powder material, titanium alloy 3D printing piece and manufacturing method of titanium alloy 3D printing piece
CN121610681A